Effect of oat to flour ratio on stickiness of the cookie dough - Mohd Jais, Nurain; Mohd Basri, Mohd Salahuddin (Malaysian Society of Agricultural Engineers, 2019)
Texture attributes, such as stickiness of grain-based food is important to consumers and manufacturers (McManuis, 2001). Descriptive method such as Texture Profile Analysis (TPA) is used in order to describe the textural properties of the cookie dough. By using TPA, the structure of the food can be emphasize. Mixture formulation of cookie dough based on five different cup ratios of oat to flour which are 1:1, 1:1.25, 1:1.5, 1:1.75 and 1:75. The ratio of 1:1.5 is the basic mixture formulation provided by the SME’s cookies company. The calculated weight was rounded off to the nearest whole number. Example, for 1.8 cups of oat at ratio 1:1.5, the total weight required was 1.8 cups times 94 grams which equal to 169.2 grams. After rounded off to the nearest whole number, the weight required was 169 grams. Similar calculation method was used to calculate the weight of flour. For each ratio of oat to flour, the total cup required for every mixing process was 4.5 cups. As results, different ratio of oat to flour had a significant effect on the dough stickiness where cookie dough with ratio 1:1.75 flour have the highest stickiness value while cookie dough with ratio 1:1.25 have the lowest stickiness value. This is because the higher flour content contains higher starch which contribute to higher moisture content. Hence, the dough with more flour is more sticky. The current study indicated a high potential in developing fiber-rich cookies with large inclusion with composition of 1:1.25 of oats and flour respectively which produced a less sticky dough. Thus, the increasing of oat and flour content in the formulation show a significant effect on dough stickiness.